Solving non-convex economic dispatch problem using computational intelligence technique - Mansor M.H.; Othman M.M.; Musirin I.; Saleh S.A.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Computer programming; Immune system; Scheduling; Artificial Immune System; Computational intelligence techniques; Economic Dispatch; Evolutionary programming algorithms; Log-normal; Non-convex economic dispatches; Reliability test system; Valve-point loading effect; Electric load dispatching